Intramyocellular Lipid Is Associated with Visceral Adiposity, Markers of Insulin Resistance, and Cardiovascular Risk in Prepubertal Children: The EPOCH Study - Brumbaugh, David E. (Endocrine Society, 2012)
CONTEXT: The intramyocellular deposition of lipid associates with metabolic dysregulation in adolescents and adults. Relatively little is known about the deposition of fat in muscle before the onset of puberty. OBJECTIVE: Our objective was to describe the relationship between intramyocellular lipid (IMCL) accumulation and 1) visceral adiposity and 2) markers of insulin resistance and cardiovascular disease risk in a cohort of prepubertal and early pubertal children. STUDY DESIGN: Data were collected as part of a retrospective cohort study, Exploring Perinatal Outcomes among Children (EPOCH). Multiple linear regression models were constructed for data analysis. RESULTS: A total of 441 children participated in the study (226 prepubertal, 215 early pubertal). In prepubertal children, there was a significant relationship between IMCL and visceral fat (parameter estimate 0.019, P = 0.002) that remained after controlling for body mass index. Independent of overall adiposity, in all children, IMCL was associated with the triglyceride to high-density lipoprotein ratio (parameter estimate 0.1418, P = 0.002). CONCLUSIONS: This study demonstrates a concerning and related pattern of IMCL and visceral fat deposition in prepubertal children. Intramuscular fat deposition is linked to markers of insulin resistance and cardiovascular disease risk.